Analisis Hukum terhadap Pelaku Aborsi menurut Pasal 75 Ayat (2) Jo Pasal 194 Undang-Undang Nomor 17 Tahun 2023 tentang Kesehatan: Analisis Putusan Nomor:482/Pid.Sus/2021/Pn.Ckr - Arifin, Zaenal; Chandra, Mochamad Haris (Sekolah Tinggi Ilmu Hukum (STIH) Prof Gayus Lumbuun, 2024)
Aborsi has always been a hot topic, especially regarding abortion provocatus criminalis, which is increasingly common in modern society and industries experiencing globalization. What is the criminal responsibility of abortion perpetrators based on Article 75 paragraph (2) in conjunction with Article 194 of Law No. 17 of 2023 concerning Health? To find out the legal responsibility of the perpetrator of an abortion based on Article 75 paragraph (2) in conjunction with Article 194 of Law No. 17 of 2023 concerning Health. There are also medical records that are useful in determining something related to a doctor's actions. Medical records have a very important function and role in the health sector, including in law enforcement efforts, especially proving malpractice cases in the medical field. The police should be more careful in handling abortion cases and perhaps this can be done by approaching teenagers by providing education about the dangers of having an abortion, the negative impacts of promiscuity, and the police should be able to work together with doctors or midwives who know about abortion and if Any teenager who comes to a doctor or midwife to have an abortion should be reported to the police.